Cytotoxic T cells and their activation status are independent prognostic markers in meningiomas - Rapp, Carmen; Dettling, Steffen; Liu, Fang; Ull, Anna Theresa; Warta, Rolf; Jungk, Christine; Rösch, Saskia; Mock, Andreas; Sahm, Felix; Schmidt, Melissa; Jungwirth, Gerhard; Zweckberger, Klaus; et al. (Clinical cancer research, 2019)
Purpose: Clinically aggressive meningiomas (MGMs) are rare but treatment-resistant tumors in need for more effective therapies. Because tumor-infiltrating T lymphocytes (TILs) are essential for successful immunotherapy, we assessed TIL numbers and their activation status in primary (p-) and recurrent (r-) meningiomas and their impact on survival. - Experimental Design: Presence of TILs was analyzed in 202 clinically well-annotated cases (n = 123 pMGMs and n = 79 rMGMs) focusing on higher-grade meningiomas [n = 97 World Health Organization (WHO) °II, n = 62 WHO°III]. TILs were quantified by a semiautomated analysis on whole-tissue sections stained by multicolor immunofluorescence for CD3, CD8, FOXP3, and programmed cell death protein 1 (PD-1). - Results: Median T-cell infiltration accounted for 0.59% TILs per total cell count. Although there were no significant WHO°-dependent changes regarding helper (CD3+CD8−FOXP3−) and cytotoxic (CD3+CD8+FOXP3−) TILs in pMGMs, higher number of cytotoxic TILs were associated with an improved progression-free survival (PFS) independent of prognostic confounders. rMGMs were characterized by lower numbers of TILs in general, helper, and cytotoxic TILs. The additional analysis of their activation status revealed that a proportion of PD-1+CD8+ TILs within the TIL population was significantly decreased with higher WHO grade and in rMGMs. Furthermore, lower proportions of PD-1+CD8+ TILs were associated with inferior PFS in multivariate analyses, arguing for PD-1 as activation rather than exhaustion marker. - Conclusions: We identified higher numbers of CD3+CD8+FOXP3− TILs and proportions of PD-1-expressing CD3+CD8+FOXP3− TILs as novel biomarkers for better survival. These findings might facilitate the selection of patients who may benefit from immunotherapy and argue in favor of an intervention in primary rather than recurrent tumors.